DYNAMIC MODELING AND SIMULATION ANALYSIS OF A ROLLING BEARING-ROTOR SYSTEM - LV Yun; TONG DaPeng; TIAN Ye; LAI YaHui (Jixie qiangdu)
Considering the reflection and influences of nonlinear touch rolling bearing towards dynamic,the theme of this paper focus on the slight axe experiment flat roof and comprise pedestal as well as rolling bearing. Use the way of variable step size "Runge-kutta"to make a solution through the model of dynamic. On the other side,the bifurcation diagrams also investigate the mass eccentricity for different rotors and its rotate speed. By the way,the evident change of shaft stiffness and supporting damp appear more obvious. The orbits plot,Poincare pictures and its frequency spectrum analyzed the signal features under the various situations. Through the experiment we can safely draw the conclusion that with the increase of the speed,vibrancy is higher up,the area of periodic locomotion will become narrow,so keep clear of the chaos sedulously when it happen to add up speed. The shaft stiffness have a great influence to the rotors,bulky stiffness can improve the stabilization to the rotors. But it will pass the vibration to the rotors. Meanwhile,avoid the bulky mass eccentricity is necessary if you want to keep a normal area and lower the impact speed. Supporting damp makes difference to the rotors vibration,with the addition of supporting damp,vibrancy will be reduced,the area of Chaos locomotion will become narrow,the area of periodic locomotion will be higher up. As a result,the system will be stabilized.